2002
DOI: 10.1073/pnas.042650399
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic flexibility and gating mechanism of the potassium channel KcsA

Abstract: The gating mechanism of the potassium channel KcsA was studied by normal mode analysis. The results provided an atomic description of the locations of the pivot points and the motional features of key structural elements in the gating process. Two pivot points were found in the motions of the inner TM2 helical bundle that directly modulate the size of the central channel pore. One point is an intrasubunit hinge point that sharply divides the structural flexibility between the more rigid selectivity filter and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 31 publications
7
50
1
1
Order By: Relevance
“…Although both features are present in the sequence of most potassium ion channels, they have been considered as leading to a mutually exclusive mechanism of gating [11, 12]. In contrast, our results suggest that these two features may complement each other, as suggested previously [7, 60, 61]. The bend at G229 clearly plays the main role in the formation of the S6 helical bundle that constitutes the activation gate, but the associated conformational change starts at G220, allowing the formation of a hydrated inner vestibule while keeping the extracellular region of the pore relatively rigid.…”
Section: Discussionsupporting
confidence: 68%
“…Although both features are present in the sequence of most potassium ion channels, they have been considered as leading to a mutually exclusive mechanism of gating [11, 12]. In contrast, our results suggest that these two features may complement each other, as suggested previously [7, 60, 61]. The bend at G229 clearly plays the main role in the formation of the S6 helical bundle that constitutes the activation gate, but the associated conformational change starts at G220, allowing the formation of a hydrated inner vestibule while keeping the extracellular region of the pore relatively rigid.…”
Section: Discussionsupporting
confidence: 68%
“…This hinge contributes to the plasticity of the coupling between the two ends of the channel. This phenomenon was not observed in calculations of the individual subunits (data not shown), and previous normal mode analysis attributed it to the intersubunit contacts within the tetrameric structure [41]. The motion of the intracellular termini of the inner helices away from the pore at Ala108 was observed as part of the gate-opening process in recent atomistic normal-mode and Monte Carlo simulations [32].…”
Section: Resultsmentioning
confidence: 81%
“…The hinge was observed both in the isolated subunit (second mode; Figure 3A) and the tetramer (fifth mode; Figure 3B), which indicates that it is also an intrinsic property of the subunit. The presence of a hinge in this region has emerged in EPR studies [5] and in previous normal-mode calculations [41]. Interestingly, a recent normal-mode/Monte Carlo study showed that pore opening was initiated by the motion of the preceding residue, i.e., Ala108 [32].…”
Section: Resultsmentioning
confidence: 85%
“…Similar to other ion channels such as the potassium channel and nicotinic acetylcholine receptor, ASIC1 should undergo large-scale (occasionally global) conformational deformations when eliciting cellular functions, such as gating [5,6]. Simulating global conformational changes of proteins is beyond the scope of the conventional molecular dynamics and Monte Carlo simulation methods [6].…”
mentioning
confidence: 99%